Analysis of Inclusive School Implementation Based on Structural Functional Theory in Senior High Schools in Surakarta - Azhar, Mohamad Rizki; Liestyasari, Siany Indria (Jurnal Paedagogy, 2025)
This study analyzes the implementation of inclusive schools through Structural Functional Theory in senior high schools in Surakarta City. Utilizing a qualitative descriptive approach, this research focuses on two inclusive schools, SMAN 8 Surakarta and SMA Muhammadiyah 6 Surakarta, as its subjects. Data were gathered through in-depth interviews, observations, and document analysis involving school principals, teachers, and educational staff as key informants, and the collected data were analyzed using Miles and Huberman’s interactive model, which encompasses data reduction, data presentation, and conclusion drawing.. The findings reveal that the two schools employ distinct strategies: SMAN 8 Surakarta prioritizes structured policies, regular teacher training, and facility development, whereas SMA Muhammadiyah 6 Surakarta adopts a community-centered approach by engaging parents and the local community, despite facing infrastructural limitations. By applying the AGIL framework (Adaptation, Goal, Integration, and Latency), this study highlights fundamental challenges, including inadequate teacher training, restricted resources, and the absence of formal policies. Consequently, the study suggests enhancing governmental support, fostering stronger partnerships between schools and communities, and ensuring continuous professional development for teachers to create a more effective and sustainable inclusive education system.